Ethical consequences of prenatal and perinatal psychology - Jankovský, Jiří (Journal of Nursing, Social Studies and Public Health, 2014)
This contribution deals with the ethical issues directly related to prenatal and perinatal psychology that views human life as encounters, continuity and dialogue. The success of the life of a newborn baby is already predetermined in the prenatal period, which depends primarily on the psychological state (mood) of the mother. Confucius was aware of this fact as early as the 6th century BC. Moreover, Aristotle dealt with the issue regarding the beginning of life (4th century BC.) followed by St. Thomas Aquinas in the 13th century. What is surprising is the extent to which their views correspond to our current knowledge. Of course, it depends on our point of view, whether we approach solving these issues in terms of philosophy, law, medicine, psychology or theology. The author also deals with some of the modern issues associated with the current crisis of the family, as is the trend of more “singles”, falling marriage rates, the promiscuous behaviour of couples out of wedlock, denial of paternity, low birth rate, induced abortions, irresponsibility and lack of appropriate identification patterns in the family, and so forth. It draws attention to some of the possibilities and capacities of reproductive medicine, such as cryopreservation of sperm, oocytes and embryos, spare gestation, issues related to genetic engineering and consulting, gender selection and the like.
Keywords: Ethical Review; otcovské chování; etické zhodnocení; perinatální péče; lidé; Perinatal Care; Maternal Behavior; Family Conflict; reprodukční lékařství; genetické poradenství; maternofetální vztahy; Object Attachment; prenatální péče; rodinné vztahy; Family Relations; Prenatal Care; mateřské chování; Maternal-Fetal Relations; Reproductive Medicine; Paternal Behavior; připoutání k objektu; Genetic Counseling; konflikt v rodině; Humans